Comparing the Separation of Powers in Indonesia and Russia: Constitutional Structures and Political Impacts - Imran Eka Saputra; Ali Rahman; Ildar Begishev (Jurnal Dinamika Hukum, 2025)
The distribution of power in Indonesia and Russia shows differences in the implementation of the principle of separation of powers. Indonesia, as a unitary state with a presidential system, faces challenges in maintaining balance between the central and regional governments. Meanwhile, Russia, as a federal state with a semi-presidential system, remains centralized, with executive power largely dominated by the president. This study aims to analyze the model of power distribution in the constitutional law of Indonesia and the Russian Federation based on their respective governmental systems, as well as to identify the advantages, disadvantages, and implications for government stability in both countries. This research employs a normative legal method with a statutory, comparative, and conceptual approach to analyze the power distribution model in Indonesia and Russia based on their constitutions and relevant regulations, using library research techniques and qualitative analysis. The findings indicate that the power distribution models in Indonesia and Russia differ according to their respective governmental systems. Indonesia adopts a presidential system with strong checks and balances between the executive, legislative, and judicial branches, while Russia follows a semi-presidential system that grants dominant authority to the president. Indonesia emphasizes power balance through democracy and decentralization, though it faces challenges such as political gridlock and slow bureaucracy. Conversely, Russia enjoys stronger political stability due to executive dominance, but at the risk of weakening checks and balances and limiting political freedoms. Thus, the governmental systems in both countries have their own advantages and disadvantages in influencing stability and governance effectiveness.